THE EFFECT OF THE “TANDEM” STIMULATOR ON THE GROWTH AND DEVELOPMENT OF COTTON PLANTS - qizi, Xolboyeva Muxayyo Boboyor; Mardanakulovich, Tadjiyev Karim (Research Focus International Scientific Journal, 2026)
This article studies the effect of the "Tandem" stimulator on the growth and development of cotton. According to the results of the study, the use of the stimulator accelerates the development of vegetative and generativ organs of the plant, increases productivity, and increases resistance to stress factors.